E-worksheet assisted by Liveworksheets: Innovation in learning media for chemical bonds based on ethnoscience to improve critical thinking skills of high school students - Shafnahriyah, Zuhaira; Sukarmin, Sukarmin (Indonesian Journal of Science and Mathematics Education, 2026)
The abstract nature of chemical bonding often leads to limited conceptual understanding and weak critical-thinking skills, underscoring the need for innovative, contextually relevant learning media. Therefore, this study integrates an ethnoscience approach with Liveworksheets-assisted interactive tasks to support contextual learning and enhance students’ higher-order thinking in chemistry. This study aimed to develop an ethnoscience-based e-worksheet supported by Liveworksheets and to examine its effectiveness in enhancing high school students’ critical thinking skills. A Research and Development (R and D) method using the 4D model was implemented, encompassing expert validation, practicality assessment through student response questionnaires, and effectiveness testing using a one-group pretest–posttest design involving 36 eleventh-grade students at a public senior high school. The developed e-worksheet was found to be highly valid and very practical, achieving a practicality score of 96.5%. Effectiveness results indicated a significant improvement in students' critical thinking skills, with an average N-gain of 0.73 in the high category across interpretation, analysis, evaluation, explanation, and inference indicators. These findings demonstrate that integrating ethnoscience and Liveworksheets through e-worksheet promotes meaningful chemistry learning and the development of critical thinking. The findings imply that ethnoscience-based interactive multimedia is an effective instructional resource for supporting contextual and higher-order thinking-oriented chemistry learning.